The 2021 energy crisis: Implications for China's energy market and policies - Bassam Fattouh; Michal Meidan; Philip Andrews-Speed (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2022)
In late 2021, China experienced a severe electricity supply crisis that affected 20 provinces. Industrial activity was curtailed, and even households suffered prolonged outages in some areas. The country is no stranger to periodic energy supply shortages and in many outages in the past, the principal causes involved either poor policy coordination or a clash between market forces and government plans and administrative measures. This time it was no different. This issue of the Oxford Energy Forum analyses the 2021 energy crisis in China, its causes and its implications for domestic energy markets and the country's low-carbon energy transition.
Keywords: 330